Functionalized Wood: A Green Nanoengineering Platform for Sustainable Technologies - Zhang, Tuo; Gu, Mingwei; Liu, Yizhu; Chen, Guangyao; Zhang, Haiyang; Chen, Liguo; Zhou, Xingwen; Sun, Lining; Wen, Zhen; Zhou, Yunlei; Huang, Haibo (Nano-Micro Letters, 2026)
Wood, once regarded primarily as a structural material, possesses rich physicochemical complexity that has long been underexplored. In the context of industrialization and carbon imbalance, it is now emerging as a renewable and multifunctional platform for green nanotechnologies. Recent advances in wood nanotechnology have enabled the transformation of natural wood into programmable substrates with tailored nanoarchitectures, establishing it as a representative class of bio-based nanomaterials. This review systematically categorizes wood-specific nanoengineering strategies—including thermal carbonization, laser-induced graphenization, targeted delignification, nanomaterial integration, and mechanical processing—highlighting their mechanisms and impacts on wood’s multiscale structural and functional properties. Importantly, these functionalization strategies can be flexibly combined in a modular, “Lego-like” manner, enabling wood to be reconfigured and optimized for diverse application scenarios. We summarize recent progress in applying functionalized wood to sustainable technologies such as energy storage (e.g., metal-ion batteries, Zn–air systems, supercapacitors), water treatment (e.g., adsorption, photothermal filtration, catalytic degradation), and energy conversion (e.g., solar evaporation, ionic thermoelectrics, hydrovoltaics, and triboelectric nanogenerators). These studies reveal how nanoengineered wood structures can enable efficient charge transport, selective adsorption, and enhanced light-to-heat conversion. Finally, the review discusses current challenges—such as scalable fabrication, material integration, and long-term environmental stability—and outlines future directions for the development of wood-based platforms in next-generation green energy and environmental systems. Highlights: 1 The intrinsic hierarchical, anisotropic, and porous architecture of wood provides a structurally programmable scaffold that supports subsequent nanoengineering strategies, enabling multiscale property modulation for diverse sustainable applications. 2 Wood-specific hierarchical nanoengineering strategies—including carbonization, delignification, laser-induced graphene formation, and nanomaterial integration—are systematically categorized to enable tunable structures and properties across multiple length scales. 3 Functionalized wood with nanostructures enables sustainable solutions in energy storage (e.g., Zn–air batteries, supercapacitors), water treatment (e.g., adsorption, filtration), and renewable power generation (e.g., solar-thermal, thermoelectric and hydrovoltaic systems).